Development of Research-Based Flowering Plants Catalog as a Supplement of Biology Teaching Materials in High School (Universitas Negeri Semarang, 2019)
Species richness of flowering plants in Bandungan area of Semarang is one of the potency that can be used as a biology learning resources. Those pontency can be developed as teaching material. This study aims to identify flowering plants in Bandungan area that are used as material for developing learning catalogs. This study uses the Research and Development (R&D) approach with the ADDIE model. Catalog are validated by material experts and media experts before use. The catalog trial was conducted on 40 students of X IPA classes using the one group pretest-posttest design. The results show that the catalog is declared 'very valid' by material experts and media experts with an average percentage of 88.72%. Catalog stated to be effective in improving learning outcomes with an average N-gain of 0.55 ('medium' criteria). Catalog get positive responses from teacher and students in the 'very worthy’ category with an average percentage of 88.11%.